Health and Wealth in America - Weeks, Bill; Lavista Ferres, Juan M.; Weinstein, James (International Journal of Public Health, 2024)
Health and wealth has a long-established relationship, and recent studies found that local economic improvements are associated with improved population health measures [1, 2]. Building on this research, wealth redistribution has been proposed as a way to extend United States longevity and narrow the US-OECD average mortality gap [3]. To address health inequities, public policy has focused on understanding the social determinants of health, defined by the World Health Organization as “the non-medical factors that influence health outcomes” and “the conditions in which people are born, grow, work, live, and age and the wider set of forces and systems shaping the conditions of daily life.” Many studies found associations between exposure to worse social determinants conditions and worse health outcomes.